"Producción del cultivo de pepino (Cucumis sattivus) aplicando diferentes láminas de riego por goteo bajo invernadero en la finca la María de la UTEQ 2015". - Zurita Castro, Sandro Jonatan (2016)
This research was made on the grounds of the estate of Mary, belonging to the State Technical University Quevedo located at Km 71¬¬¬¬/2 vía Quevedo. - El Empalme, Province of Los Rios, whose coordinates geographical are: 79th 32 '24 "west longitude 01st 05' 18", at an altitude of 75 meters. The cucumber belongs to the Cucurbitaceae family and its scientific name is Cucumis sativus is a herbaceous, annual and creeping plant cover bristling, of fasiculadas roots development rather superficial, with the highest concentration of roots between 25 and 30 cm (Carlos Bojacá Oscar Monsalve, 2012). We worked with the next topic "Effect on crop production cucumber (Cucumis sativus) applying different layers of drip irrigation using tensiometers greenhouse on the farm the Mary of the UTEQ 2015" an overall objective is stated: determine the difference in crop production cucumber (Cucumis sativus), with the controlled application of drip irrigation, planted in a greenhouse. And three specific objectives was also raised. In this research results it was obtained using a drip irrigation system with the application of sphygmomanometers with replacement blades ranging from 30, 45, and 60% and a control reset to 0% was called. Fieldwork was conducted in a greenhouse using an area of 128 m2 in which one study factor, irrigation levels (four), 4 treatments which are established studied; Consumption 30% Consumer 45% Consumer 60% in consumption field capacity, control without replacement. Design completely lift (DCA) was used to evaluate the water performance of each of the sheets applied to drip irrigation system studying 4 treatments and 4 repetitions, the Tukey test was used at 95% probability. They obtubieron resultdos both production and performance where sheet showed 30% higher performance below the lamina of 0% that showed less production. Keywords: irrigation, replacement, greenhouse, sphygmomanometers